2021
DOI: 10.1002/ctm2.525
|View full text |Cite
|
Sign up to set email alerts
|

RNA N6‐methyladenosine modification in the lethal teamwork of cancer stem cells and the tumor immune microenvironment: Current landscape and therapeutic potential

Abstract: N6‐methyladenosine (m6A), the newest and most prevalent layer of internal epigenetic modification in eukaryotic mRNA, has been demonstrated to play a critical role in cancer biology. Increasing evidence has highlighted that the interaction between cancer stem cells (CSCs) and the tumor immune microenvironment (TIME) is the root cause of tumorigenesis, metastasis, therapy resistance, and recurrence. In recent studies, the m6A modification has been tightly linked to this CSC‐TIME interplay, participating in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 141 publications
(402 reference statements)
1
20
0
Order By: Relevance
“…In addition, m6A methyltransferase complex is mainly composed of METTL3 (methyltransferase-like 3), METTL14 (methyltransferase-like 14), and WTAP (Wilms tumor 1-associated protein), which act as "writer" to catalyze methylation processes, whereas FTO (fat mass and obesity associated protein) and ALKBH5 (alkB homolog 5) act as demethylases ("eraser"). The ultimate fate of m6A methylated mRNA depends on the "reader" (e.g., YTHDF1, YTHDF2, and YTHDF3) that recognizes them, affecting mRNA translation, stability, splicing, and nuclear transportation (7). Numerous m6A targets have been involved in cell tissue development and stem cell self-renewal and differentiation, circadian rhythm regulation, T-cell homeostasis, mouse fertility, postnatal development of the mouse cerebellum, innate immune response, ultraviolet-induced DNA damage response, and dendritic cell antigen presentation (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, m6A methyltransferase complex is mainly composed of METTL3 (methyltransferase-like 3), METTL14 (methyltransferase-like 14), and WTAP (Wilms tumor 1-associated protein), which act as "writer" to catalyze methylation processes, whereas FTO (fat mass and obesity associated protein) and ALKBH5 (alkB homolog 5) act as demethylases ("eraser"). The ultimate fate of m6A methylated mRNA depends on the "reader" (e.g., YTHDF1, YTHDF2, and YTHDF3) that recognizes them, affecting mRNA translation, stability, splicing, and nuclear transportation (7). Numerous m6A targets have been involved in cell tissue development and stem cell self-renewal and differentiation, circadian rhythm regulation, T-cell homeostasis, mouse fertility, postnatal development of the mouse cerebellum, innate immune response, ultraviolet-induced DNA damage response, and dendritic cell antigen presentation (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a strong correlation between TME and m 6 A modifications, especially in immune cell infiltration. 33 , 34 ALKBH5 modulates the therapeutic response of anti-PD-1 by regulating lactate and inhibiting the accumulation of immune cells in TIME, thereby reducing the outcome of immunotherapy in melanoma, colorectal cancer and potentially other cancers. 35 FTO enhances protein expression by regulating the m 6 A modification of JUNB and CEBPB genes, thereby promoting tumour glycolysis and inhibiting T cell effects.…”
Section: Introductionmentioning
confidence: 99%
“…This modification is regulated by the m6A methyltransferases (writers) methyltransferase-like 3 (METTL3), METTL14, METTL16, Zinc finger CCCH domain-containing protein 13 (ZC3H13), and Homo sapiens RNA binding motif protein 15 (RBM15); demethylases (erasers) fat mass- and obesity-associated protein (FTO) and alkB homolog 5 (ALKBH5); and binding proteins (readers) YTH domain family (YTHDF) proteins such as YTHDF1-3 and YTHDC1-2, and insulin-like growth factor 2 messenger RNA-binding proteins (IGF2BP1-3) [ 8 ]. These proteins are frequently upregulated or downregulated in human cancer tissues to control cell differentiation via altering splicing, RNA processing, protein translation, microRNA binding, and RNA-protein interaction [ 9 ]. For example, METTL14-dependent m6A methylation-mediated hepatocyte nuclear factor 3γ mRNA reduction rendered hepatocellular carcinoma dedifferentiation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%